2015
DOI: 10.1016/j.addbeh.2015.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of other tobacco use in a community sample of young adults

Abstract: Background young adult use of alternative nicotine and tobacco products (ANTPs) has increased dramatically since 2000. While recent studies address ANTP prevalence, relatively little is known about predictors of use. This secondary analysis examined demographic, personality, and other substance use factors as predictors of past month ANTP use. Methods community participants (n = 319; 51% female) completed an online survey during the initial stage of a larger study, for which all were required to have smoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
13
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 38 publications
3
13
0
6
Order By: Relevance
“…In contrast, perceived stress was not associated with use. Consistent with previous research, (Berg et al, 2011; Doran & Trim, 2015; Goodwin et al, 2014) alcohol use also predicted hookah likelihood and frequency. To our knowledge, this is the first study to examine the relationship between stressful life events and hookah use.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, perceived stress was not associated with use. Consistent with previous research, (Berg et al, 2011; Doran & Trim, 2015; Goodwin et al, 2014) alcohol use also predicted hookah likelihood and frequency. To our knowledge, this is the first study to examine the relationship between stressful life events and hookah use.…”
Section: Discussionsupporting
confidence: 88%
“…Hookah has been associated with personality traits, including impulsivity and social comparison orientation (Berg, Schauer, Asfour, Thomas, & Ahluwalia, 2011; Doran & Trim, 2015; Fielder, Carey, & Carey, 2012). Hookah use has also been related to cognitions, including affect regulation expectancies (Doran & Brikmanis, 2016).…”
mentioning
confidence: 99%
“…Previous research has found an association between sensation seeking and OTP use (Doran & Trim, 2015; Enofe et al, 2014). Interestingly, sensation seeking predicted overall OTP frequency but was not related to frequency of any individual OTP.…”
Section: Discussionmentioning
confidence: 95%
“…Impulsive individuals are prone to engaging in immediately rewarding behaviors (e.g., nicotine intake) regardless of potential long-term consequences (Bloom et al, 2014) and appear to smoke cigarettes for positive and negative reinforcement (Doran et al, 2007). Impulsivity has been linked to e-cigarette, hookah, and cigar use (Doran & Trim, 2015; Enofe et al, 2014; Fielder et al, 2012; Leventhal et al, 2016; Sterling et al, 2013). Specifically, sensation seeking and positive urgency were associated with the likelihood of recent OTP use (Doran & Trim, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation